2019
DOI: 10.1111/apt.15520
|View full text |Cite
|
Sign up to set email alerts
|

Letter: should we intensify infliximab in acute severe ulcerative colitis?

Abstract: LINKED CONTENTThis article is linked to Sebastian et al and Sebastian papers. To view these articles, visit https://doi.org/10.1111/apt.15456 and https://doi.org/10.1111/apt.15569.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…To view these articles, visit https://doi.org/10.1111/apt.17753 and https://doi. org/10.1111/apt.17873 Matthias Lenfant 1,2 Bram Verstockt 1,2 João Sabino 1,2 Séverine Vermeire 1,2 Marc Ferrante 1,2…”
Section: Ack N O Wle D G E M Entsmentioning
confidence: 99%
See 1 more Smart Citation
“…To view these articles, visit https://doi.org/10.1111/apt.17753 and https://doi. org/10.1111/apt.17873 Matthias Lenfant 1,2 Bram Verstockt 1,2 João Sabino 1,2 Séverine Vermeire 1,2 Marc Ferrante 1,2…”
Section: Ack N O Wle D G E M Entsmentioning
confidence: 99%
“…We read with great interest the letter from Dr. Laharie discussing our study on the predictive role of a segmental endoscopic assessment in ulcerative colitis by means of the modified Mayo endoscopic score (MMES). 1,2 The author focussed on the emerging role of noninvasive monitoring tools such as faecal calprotectin and intestinal ultrasound. Furthermore, he questioned the role of endoscopy as a monitoring tool for ulcerative colitis in future.…”
mentioning
confidence: 99%
“…For instance, it has been proposed that, in patients with perianal fistulizing CD, higher than usual infliximab TLs are required to induce healing [93][94][95]. It has also been suggested that patients with acute severe ulcerative colitis (ASUC) might benefit from an optimized induction regimen (with an additional infusion at week 1), even though results have been inconsistent so far [96][97][98]. Furthermore, there is evidence that therapeutic levels depend also on the target considered: more ambitious targets might require higher TLs [99,100].…”
Section: Therapeutic Drug Monitoringmentioning
confidence: 99%
“…Laharie and Riviere for their thoughtful comments on the use of infliximab rescue therapy and accelerated induction in the setting of steroid-refractory acute severe colitis as reported in our recent paper. 1,2 I fully appreciate their own observation 3 that the 1-year colectomy rates have not declined based on randomised controlled trial evidence.…”
mentioning
confidence: 95%